Individual work with students of orchestral section at the faculty of arts in the class of principal and additional music instruments (Pedagogy of Higher and Secondary Education, 2016)
The article discusses key issues concerning the planning and organization of the educationalprocess during the individual lessons by principal and additional music instrument. The textconsiders a various educational aspects, which will be introducedfor improvement of moderneducation in the conditions of study this discipline in further.The content of this paper deals with the essence of its conception in the conditions ofstudying at the Art faculty in higher educational institutions.The article considers main problems, which influence the quality of professional training offuture music art teachers in Ukraine.The aim of this article is to define and decide common tasks, related to the development ofprofessional approach to main questions, concerning the individual training to instrumental-performing activity into the orchestra, ensemble and solo at the Art faculty.The subject of the paper is to present the importance of this study for future music artteachers and professional music training in general.The article begins with short discussion of certain problems in the field of professionalinstrumental-performing activity. Authors of this paper explain the main methodical approaches,which will needed for mutual work in pedagogical activity between the students and teachers at the instrumental disciplines, such as: formation of professional skills of playing the music instrument,development of professional approach to the playing at the folk-instrumental ensemble andorchestra are defined and established.It should be emphasized that main problems of professional readiness will depend on thelevel of following conceptions, such as: analysis of musical forms, interpretation of music piece inthe process of performance, interrelation and interdependence between the different kinds of artisticactivity for improvement of professional readiness results.Methodological solutions of problematic situations that appear during the development of
Keywords: principal music instrument; additional music instrument; individual work; agogics; phrasing; interpretation; ensemble; orchestra of folk instruments; learning process; orchestral section